Germination and Seedling Leaf Chlorophyll Content of Wheat (Triticum aestivum L.) Grown under Industrial Wastewater Condition - Pramanik, SK; Sikder, S (The Agriculturists, 2020)
The tobacco industry is one of the biggest industries in the world generates and disposes large quantities of wastewater in the environment which may be toxic to the plant, animal, public health as well as environment. Therefore, an experiment was conducted during November, 2019 at Crop Physiology and Ecology Laboratory, Hajee Mohammad Danesh Science and Technology University, Dinajpur, Bangladesh to observe the effects of tobacco industry wastewater on germination, early seedling growth and seedling leaf chlorophyll content of wheat (TriticumaestivumL.). Three wheat genotypes (BARI Gom 28, BARI Gom 29 and BAW 1177) and two growing conditions (normal tap water and tobacco industry wastewater) were assigned in a completely randomized design with three replications in germination test. Results showed that germination characteristics, seedling growth and chlorophyll content in leaf of seedling significantly influenced by wheat genotype, growing condition and their interaction. Irrigation with tobacco industry wastewater lowered the germination percentage, rate of germination, co-efficient of germination and vigor index. However, seedlings irrigated with tobacco industry wastewater produced longer shoot and root as compared to seedlings irrigated with tap water. Similarly, tobacco industry wastewater increased the shoot and root dry weight but reduced the chlorophyll content in leaf of seedling. Among the three wheat genotypes, BAW 1177 performed better under both tap water and wastewater conditions regarding germination, early growth and chlorophyll content in leaf of seedling. The Agriculturists 2020; 18(1) 10-17